2010
DOI: 10.1111/j.1756-8765.2010.01114.x
|View full text |Cite
|
Sign up to set email alerts
|

Naïve Realism: Folk Fallacies in the Design and Use of Visual Displays

Abstract: Often implicit in visual display design and development is a gold standard of photorealism. By approximating direct perception, photorealism appeals to users and designers by being both attractive and apparently effortless. The vexing result from numerous performance evaluations, though, is that increasing realism often impairs performance. Smallman and St. John (2005) labeled misplaced faith in realistic information display Naı¨ve Realism and theorized it resulted from a triplet of folk fallacies about percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 40 publications
2
34
0
Order By: Relevance
“…When we consider an empirical result, we should pay attention to what type of 3D has been tested. Furthermore, as in all visualizations, related design choices (Oh et al, 2011) such as interactivity (e.g., Amini et al, 2014), use of color (e.g., Brychtová & Çöltekin, 2016), or degree of realism e.g., phototextures, virtual environments (e.g., Boér et al, 2013;Smallman & Cook, 2011).…”
Section: Conceptual Organization Of Current Empirical Studiesmentioning
confidence: 99%
“…When we consider an empirical result, we should pay attention to what type of 3D has been tested. Furthermore, as in all visualizations, related design choices (Oh et al, 2011) such as interactivity (e.g., Amini et al, 2014), use of color (e.g., Brychtová & Çöltekin, 2016), or degree of realism e.g., phototextures, virtual environments (e.g., Boér et al, 2013;Smallman & Cook, 2011).…”
Section: Conceptual Organization Of Current Empirical Studiesmentioning
confidence: 99%
“…Additionally, participants in our study expressed preferences after having used both displays to find information about soccer games, such that they can be compared on the same merit. However, it may also be interesting to compare these judgments to preferences of people who have not (yet) used the designs since intuitions about visual representations may not always be in line with actual efficiency (Smallman & Cook 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Systematic departures from realism are valuable because they promote high-level interpretation, deemphasize irrelevant and potentially misleading details, and enable viewers to see overall trends that might otherwise be masked [56,57]. Interestingly, several studies have revealed that both novices and experts have a tendency to wrongly believe that their performance will be better with realistic compared with idealized visualizations, when the reverse is true [58]. For example, many participants viewing weather maps intuited that task-irrelevant variables and realism would improve their interpretive performance, when they were in fact hindered by their inclusion [59].…”
Section: Idealizationmentioning
confidence: 94%
“…Detailed visualizations that are appropriate for focused identification tasks are inappropriate for providing an overview of major regions [58]. Bar and box-plot graphs emphasize main effects in an experiment, whereas line graphs emphasize interactions between variables [14,69,70].…”
Section: Coordinating Interpretation Needs With Visualization Affordamentioning
confidence: 99%